Assessing Impact of Public Transportation Services on Traffic Jam in Dhaka City - Khan, Md. Tanjil Mahmud (Universitas Sanata Dharma, 2025)
This study used JASP Software for descriptive analysis and Chi-square tests. I surveyed 100 people of different backgrounds and age for their opinions. It determined that 56% of respondents were dissatisfied with the public transportation service, and 69% used public transportation daily. According to this study, 82% of people regularly experience traffic jams because it is hard to get to places, especially in places like Mirpur. Even though 64% of those who responded used buses as public transport, but only 18% wanted more buses to help ease traffic. They would rather see digital transportation systems, awareness and safety improvements. Notably, 80% of those who answered think improving public transportation services could help reduce the traffic jams in Dhaka city.